2, 6-Bis(benzimidazol-2-yl)pyridine complexes of group 14 elements. Issue 22 (10th May 2019) - Swidan, Ala'aeddeen; St. Onge, P. Blake J.; Binder, Justin F.; Suter, Riccardo; Burford, Neil; Macdonald, Charles L. B.
Abstract : Variants of the 2, 6-bis(benzimidazol-2-yl)pyridine ligand are used to synthesize novel group 14 complexes of germanium and tin. The salts are characterized by X-ray crystallography, NMR, UV-vis, and the Lewis acidity of some examples are probed. Abstract : Treatment of MCl2 (M = Ge or Sn) with 2, 6-bis(benzimidazol-2-yl)pyridine (G-BZIMPY, G = NBn, N(3, 5-CF3 )Bn, NAllyl and O) yielded the self-ionization products [G-BZIMPYMCl][MCl3 ] (1–6 ) in high yields (75–98%). Reduction reactions are examined and the nickel complexes8 and9 ([(NBn-BZIMPY)2 Ni][MCl3 ]2 ) are isolated from the reaction of Ni(COD)2 with1 and2 respectively. [NBn-BZIMPYSnCl][SnCl3 ] shows a significantly stronger MLCT band in the UV-vis absorption spectrum than its germanium counterparts, with germanium complexes exhibiting negative solvatochromism that is not observed in tin complexes.